2012
DOI: 10.1063/1.4734507
|View full text |Cite
|
Sign up to set email alerts
|

Bonding and diffusion of nitrogen in the InSbN alloys fabricated by two-step ion implantation

Abstract: We report bonding and diffusion behavior of nitrogen incorporated into InSb wafer by two-step implantation. Three nitrogen-containing regions, i.e., a surface accumulation region, a uniform region, and a tail region, were observed in the samples after post annealing. X-ray photoelectron spectroscopy measurements at different depths reveal that majority of the nitrogen forms In-N bonds in the uniform region but exists as interstitial defects in the tail region. The diffusion coefficients of nitrogen in InSb wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…It can be seen that both the FWHM value and the roughness of our grown GaSb films is comparable to other reported results, meanwhile it is worth noticing that the thickness of our grown GaSb film is extremely small compared with other works. 8,17,22,23,33,34 Therefore, our proposed growth method has the capability of growing high quality ultra-thin GaSb films on the highly mismatched substrate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be seen that both the FWHM value and the roughness of our grown GaSb films is comparable to other reported results, meanwhile it is worth noticing that the thickness of our grown GaSb film is extremely small compared with other works. 8,17,22,23,33,34 Therefore, our proposed growth method has the capability of growing high quality ultra-thin GaSb films on the highly mismatched substrate.…”
Section: Resultsmentioning
confidence: 99%
“…Antimonide based compound semiconductors have many attractive applications in infrared lasers, detectors, and high-speed electronic devices due to its wide range of electronic band gaps, unique band-structure alignments, and high electron mobility. [1][2][3][4][5][6][7][8] Moreover, as a member of the 6.1 Å family, GaSb is also an important substrate material, for example, for the growth of type II superlattice infrared lasers and detectors. [9][10][11] Although significant progress have been made in the fabrication technology of GaSb substrates in the past few years, the quality of currently commercially available GaSb substrates still cannot meet the technical requirements for the "epi-ready" substrates, due to the non-optimized oxide layer as well as the large amount of macroscopic defects on the surface.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of diffusion of atoms and radicals through polymers has previously been shown to obey the temperature activated Arrhenius relation, shown in eq . After PIII treatment, the modified layer is heavily cross-linked and carbonized, so it is not obvious that the diffusion mechanism be activated in the same way. In our analysis, we test the hypothesis that the diffusion is temperature activated. where the pre-exponential factor, D 0 , is the diffusion constant at infinite temperature (i.e., barrierless diffusion), k B is the Boltzmann constant, E A is the activation energy required for a radical to diffuse from one position to another, and T is the temperature in Kelvin.…”
Section: Theorymentioning
confidence: 99%
“…InSbN alloys have attracted attention recently due to their applications for long wavelength emission and detection [1][2][3][4][5]. It was reported that the Auger recombination rate of InSbN alloys, which is the key parameter for light sources and photodetectors, is only one-third of that of HgCdTe at equivalent band gap due to its high electron mass and conduction band nonparabolicity [6].…”
Section: Introductionmentioning
confidence: 99%